PENGARUH MODEL PROBLEM BASED LEARNING TERHADAP KEMAMPUAN PEMECAHAN MASALAH MATEMATIS PESERTA DIDIK KELAS VII UPTD SMP NEGERI 1 KEC. LAREH SAGO HALABAN - Putri, Aprilia Revita (Jurnal Edukasi dan Penelitian Matematika, 2024)
Two methods of instruction, problem-based learning (PBL) and direct instruction, were tested in the seventh grade at UPTD SMP Negeri 1 Kec. Lareh Sago Halaban TP 2023/2024. The study employed a simple random sampling procedure with a posttest-only control group design. Students enrolled in VII.1 made up the experimental group, while those enrolled in VII.3 served as the control group. This study used a quasi-experimental design for its technique. The students who utilized the Problem-Based Learning (PBL) strategy for mathematics performed better on the final exam than those who utilized the Direct Learning (DL) strategy.Keywords– Problem Solving Ability, Problem Based Learning Model, Direct Learning